PERLINDUNGAN HUKUM TERHADAP PEREMPUAN KORBAN TINDAK PIDANA REVENGE PORN (STUDI KASUS DI KEPOLISIAN DAERAH JAWA TIMUR) - Oktaviarika, Lusia Ervi; Apriyani, Maria Novita (HUKMY : Jurnal Hukum, 2024)
Indonesian women face serious threats in the form of sexual violence and sexual harassment that are difficult to obtain adequate legal protection. Cases received by Komnas Perempuan are mostly dominated by cyber violence, especially revenge porn. Revenge porn is the distribution of pornographic material for the purpose of revenge, which results in the victim being humiliated, ostracized and carried out without consent. This research explains the obstacles and solutions faced by law enforcement officials in handling revenge porn crimes. This research uses a juridical-empirical method with a statutory and conceptual approach with a descriptive method to describe existing legal problems. The data was obtained through interviews with members of the police in the Cyber field of the Special Crimes Directorate of the East Java Regional Police. The results showed several obstacles, including the lack of cyber fields at the resort and sector police levels, the lack of training for police officers and the difficulty in removing pornographic material that has been spread. In addition, public awareness of the law and gender equality is low, and victims are often reluctant to report for fear of social stigma and lack of legal protection. Proposed solutions include the addition of a cyber section at the police and police station levels, intensive training for police officers, more vigorous cyber patrols and cooperation with ECPAT, an international organization that works to protect the rights of victims of pornography.